Respuesta :
Answer:
Y = 40
Step-by-step explanation:
44 - 66y + 65y + 5 = 9
49 - y = 9
-y = -40
y = 40
Answer:
y = 40
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
- Left to Right
Equality Properties
Algebra I
- Combining Like Terms
Step-by-step explanation:
Step 1: Define
11(4 - 6y) + 5(13y + 1) = 9
Step 2: Solve for y
- Distribute: 44 - 66y + 65y + 5 = 9
- Combine like terms: -y + 49 = 9
- Isolate y term: -y = -40
- Isolate y: y = 40
Step 3: Check
Plug in y into the original equation to verify it's a solution.
- Substitute in y: 11(4 - 6(40)) + 5(13(40) + 1) = 9
- Multiply: 11(4 - 240) + 5(520 + 1) = 9
- Subtract/Add: 11(-236) + 5(521) = 9
- Multiply: -2596 + 2605 = 9
- Add: 9 = 9
Here we see that 9 does indeed equal 9.
∴ y = 40 is the solution to the equation.